FORMING INNOVATIVE THINKING SKILLS BASED ON A CREATIVE APPROACH IN PRESCHOOL-AGED CHILDREN IN THE CITY OF KOKAND - Kadirova Dildora Nadjatbekovna (The Bioscan, 2026)
The contemporary educational paradigm emphasizes the critical importance of fostering innovative and creative thinking from the earliest years. This research investigates the formation of innovative thinking skills through a creative approach in preschool-aged children (5-6 years) within the specific context of preschool educational institutions in Kokand City, Fergana region, Uzbekistan. The study is grounded in the premise that creativity is not an innate, fixed trait but a dynamic skill that can be cultivated through targeted pedagogical strategies, serving as the foundational engine for innovation. The purpose of this research was to develop, implement, and evaluate a specialized pedagogical program titled "Creative Explorers," designed to integrate principles of creative problem-solving, divergent thinking, and inquiry-based learning into the standard preschool curriculum.